2018
DOI: 10.1161/jaha.118.009459
|View full text |Cite
|
Sign up to set email alerts
|

Novel Noninvasive Assessment of Pulmonary Arterial Stiffness Using Velocity Transfer Function

Abstract: BackgroundPulmonary artery (PA) stiffness is associated with increased pulmonary vascular resistance (PVR). PA stiffness is accurately described by invasive PA impedance because it considers pulsatile blood flow through elastic PAs. We hypothesized that PA stiffness and impedance could be evaluated noninvasively by PA velocity transfer function (VTF), calculated as a ratio of the frequency spectra of output/input mean velocity profiles in PAs.Methods and ResultsIn 20 participants (55±19 years, 14 women) underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 46 publications
0
21
0
1
Order By: Relevance
“…A novel measure reflecting PA stiffness is PA velocity transfer function, which describes the influence of vessel geometry and compliance/stiffness causing frequency-dependent changes in the input velocity profile (in the proximal part of the PA) as it travels through the artery and thus produces an output velocity profile (in the distal part of the PA) [ 102 •]. PA velocity transfer function is strongly associated with invasive measures of PA impedance, stiffness, and vascular resistance.…”
Section: Estimates Of Mean Pulmonary Pressure and Pulmonary Resistancmentioning
confidence: 99%
“…A novel measure reflecting PA stiffness is PA velocity transfer function, which describes the influence of vessel geometry and compliance/stiffness causing frequency-dependent changes in the input velocity profile (in the proximal part of the PA) as it travels through the artery and thus produces an output velocity profile (in the distal part of the PA) [ 102 •]. PA velocity transfer function is strongly associated with invasive measures of PA impedance, stiffness, and vascular resistance.…”
Section: Estimates Of Mean Pulmonary Pressure and Pulmonary Resistancmentioning
confidence: 99%
“…In the literature we were able to find some observations devoted to evaluation of the pulmonary artery resistance, 11,12,[29][30][31][32] but only a few of them studied the systemic arterial stiffness. [33][34][35] Before planning this study we hypothesized the following: 1) patients with IPAH have active factors in circulation which could damage not only the pulmonary but systemic arteries too as in arterial hypertensive patients; 2) if these changes are present, they might correlate with other parameters influencing on the prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a growing interest in the use of CMR for the diagnosis and management of PH, including patients with lung diseases. Recently, we have validated a novel non-invasive CMR-derived parameter that, similar to impedance, reflects pulsatile and resistive properties of the PA 3. This approach relies on the principle that compliant PA vessel walls cause changes in the velocity profile as it travels through the PA over the cardiac cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency-dependent relationship between the input and output velocity profiles is described by a velocity transfer function (VTF), which is the relationship between the frequency spectra of input and output velocity 3. In suspected PH patients who underwent right heart catheterization, we found that VTF correlates with invasive PA impedance and the mean high-frequency modulus (MHFM) of VTF correlates with the pulmonary vascular resistance (PVR) and RV remodeling 3. Moreover, MHFM >1 accurately predicted an increased PVR 3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation